DESIGN AND IMPLEMENTATION OF BANDPASS FILTERS USING DEFECTED GROUND STRUCTURE (DGS) TECHNIQUES - KHAN, MUHAMMED TALHA (2015)
In the current era of wireless communication, there is an increasing demand of wireless components with higher reliability and performance. Due to this demand, the designers are focused on designing components that can provide minimum losses, higher selectivity, miniaturized size and increased bandwidth. The bandpass filter is one ofmost important and popular component in microwave devices and its wide applications in the field ofwireless communication is asource ofmotivation for this research work. In order to accomplish the motivational task, two different types of bandpass filters have been designed, presented and validated in this research. The foremost design is a stepped impedance resonator (SIR) bandpass filter with an I-shaped DGS in the ground plane. In conjunction with the first design, an end-coupled bandpass filter has been designed with a modified dumbbell DGS etched in ground plane.